Economic Globalization in Asean Countries: A Panel Cointegration Analysis - Kandi Dwi Pratiwi; Ika Yuni Wulansari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
Economic globalization refers to the increasing interdependence of world economies due to the growing scale of cross-border trade of commodities and services, the flow of international capital and the vast and rapid spread of technologies. The process of economic globalization in improving the economy takes time. ASEAN consists of ten countries and each has different behaviors. The development of economic globalization and the speed in increasing economic openness for each ASEAN country is different, hence the need to analyze the relationship between time and across countries using panel data. Therefore, this study aims to analyse further the effect of economic globalization on ASEAN GDP in the short and long term. It uses ICT, economic freedom, and economic openness (trade openness and financial openness) as proxies of economic globalization. The analysis method is a panel cointegration analysis and Dumitrescu-Hurlin panel causality test. The result shows that GDP growth is significantly influenced by ICT, financial openness, and economic freedom in the long term. This study reveals that economic freedom affects GDP growth positively in the long term. Conversely, ICT and financial openness have drawbacks in the long run. Meanwhile, only ICT and trade openness significantly influence GDP growth in the short term. Finally, this study reveals that economic globalization has different impacts on the economy in the short and long term.